The Effect of Urine Storage for 24 hours on Results of Urinary Leukocytes and Calcium Oxalate - Elfrida, Sabarina (International Journal of Multidisciplinary Approach Research and Science, 2024)
Urine examination is an examination often used and is most commonly done to help establish the diagnosis of a disease. The urine test consists of macroscopic, microscopic examination, and chemical examination of urine. Microscopic tests to look at erythrocytes, leukocytes, epithelial cells, thorax, bacteria, crystals, fungi and parasites. Objective: To determine the effect of urine storage for 24 hours on the results of urinary leukocytes and calcium oxalate in Binawan University staff. Method: This type of research uses primary data with a quantitative descriptive design with an analytical observation approach. This research data uses SPSS Software. This data processing is done descriptively. The tests used were the Kruskal-Wallis test and the Mann-Whitney Test Results: The frequency distribution of the description of fresh urine leukocyte results was the most 1-5 / LPB with a frequency of 26 people with a percentage of 86.7%. The distribution of the frequency of 24-hour delayed urine results was mostly 1-5 / LPB with a frequency of 29 people with a percentage of 96.7%. The distribution of fresh urine calcium oxalate was the most 1-5 / LPB with a frequency of 23 people with a percentage of 76.7%., and the frequency distribution of 24-hour delayed urine calcium oxalate results was at most 0 / LPB as many as 20 people with a percentage of 66.7%. Conclusion: In leukocyte examination, fresh urine calcium oxalate and delayed 24 hours obtained a p value of 0.00 and the results can be concluded that there is an effect of urine storage for 24 hours on the results of leukocytes and calcium oxalate urine.